Capital social em novas organizações políticas da sociedade civil - Mendonça, Pedro Kelson Batinga de (2018)
The present paper sought to study three civil society organizations in São Paulo with political impact: the Virada Política; Bancada Ativista and Rede de Ação Política pela Sustentabilidade, aiming to analyze how the Social Capital of each one is given, starting from the hypotheses that i) organizations that are more on the front of the public debate tend to have more closed cooperation models ; ii) Organizational structure, cooperation models, internal group plurality, purpose and networks of relations with other organizations are predominant factors for the strengthening of Social Capital; and (iii) more vertical organizations tend to have more fragile trust ties than more self-managed ones. These organizations were chosen because they are managed by young people and seek to broad social participation in politics and qualify Brazilian democracy. The conceptual discussion was made in two chapters – the first looks at the social and political context we are living, focusing on the global crisis of democracy and the changes in social structure caused by the technological revolution. The second presents a debate among several authors on Social Capital, althought Types of Cooperation and Nature of relational Ties. The research was done through a quantitative questionnaire sent to the three different groups and analyzed through participant observation. Among other things, the research shows that the horizontality in the management of these organizations tends to confront the internal plurality of their members and that, as much in the front of political debate, more closed they become